Empirical Review Of The Causes Of Children To Permit The Act Of Theft - Nahdhatul Botutihe (Estudiante Law Journal, 2021)
This study aims to determine the cause of children committing acts of theft. The method used in this research is empirical or sociological research methodology. This study uses a qualitative approach and sampling using purposive sampling and using descriptive analysis techniques. The results of this study indicate that the causes of children committing the crime of theft include economic factors, educational factors and environmental factors. These three factors are very influential in human life, especially for children, because some of these factors are not fulfilled, then indirectly the mindset of the child does not develop in terms of his knowledge of a crime. Looking at several factors that influence children to commit theft in general, they are interrelated. Providing education from the government and authorized institutions regarding the dangers and adverse effects of committing the crime of theft is highly expected. In addition, the local government cares for children who drop out of school or are pressured because of their weakness